2004
DOI: 10.1002/ejoc.200400363
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Conformation Analysis of New Perphosphorylated Calix[4]resorcinarenes

Abstract: The octaphosphorylation of calix [4]resorcinarenes 1 by 2-dialkylamino-1,3,2-diheterophosphorinanes 2 is described, and the effect of different factors on the structures of the resulting perphosphorylated products 3−5 was studied. Conformation analysis of these compounds by correlated 2D NMR spectroscopy and X-ray diffraction analysis was performed, and it was found that compounds 3−5, like the initial resorcinarenes 1, each have the all-cis configuration of the R groups in the methylidene bridges of the calix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…According to elemental analysis and NMR spectroscopy data, as in the previous case, solvent molecules were incorporated in octacarbamates 4a-e, apart from CsCl, to form complexes 4а•CHCl 3 Н NMR spectra exhibited two singlets for the ortho-and meta-protons of the benzene rings, one signal for protons of the methylidene bridge, and four singlets corresponding to the methylamide protons. This spectral pattern is characteristic of rccc resorcinarenes existing in the flattened boat conformation 22 . With this spatial arrangement of the octacarbamoylated resorcinarene molecule, the carbamate groups located on the vertically arranged benzene rings are spatially proximate and provide stable ion-dipole interaction with the cesium cation (Scheme 1).…”
Section: Resultsmentioning
confidence: 88%
“…According to elemental analysis and NMR spectroscopy data, as in the previous case, solvent molecules were incorporated in octacarbamates 4a-e, apart from CsCl, to form complexes 4а•CHCl 3 Н NMR spectra exhibited two singlets for the ortho-and meta-protons of the benzene rings, one signal for protons of the methylidene bridge, and four singlets corresponding to the methylamide protons. This spectral pattern is characteristic of rccc resorcinarenes existing in the flattened boat conformation 22 . With this spatial arrangement of the octacarbamoylated resorcinarene molecule, the carbamate groups located on the vertically arranged benzene rings are spatially proximate and provide stable ion-dipole interaction with the cesium cation (Scheme 1).…”
Section: Resultsmentioning
confidence: 88%
“…These data indicated the magnetic nonequivalence of phosphamide groups on the benzene rings vertically and horizontally oriented with respect to the macrocycle plane. The doubling of the signals for the protons of benzene rings (Н 3 , Н 5 ) and the upfield shift of the signals for the protons of the planar benzene rings (Н 3h ) 11 indicated that the phosphoresorcinarenes adopt the chair conformation with C 2h symmetry.…”
Section: Resultsmentioning
confidence: 98%
“…The structure of phosphoresorcinarenes 3a,b,e,f was established by correlated NMR spectroscopy and X-ray diffraction analysis. 17 It was found that compounds 3a,b,e,f, like the initial resorcinarenes 1, have the all-cis configuration of R groups at the methylidene bridges of the calixarenes system but different orientation of phenyl rings and phosphorinane fragments in respect to each another and to the macrocycle plane. Perphosphorylated resorcinarenes 3a,e with R=Me adapt a flattened cone conformation with the phosphorinane fragments on the same side of the macrocycle plane.…”
Section: Methodsmentioning
confidence: 99%